Chinese entrepreneurial capabilities and practices: case of Malaysian SME - Yeng, Wai Lau; Wei, Keng Cheah; Abdullah, Asna Atqa (2018)
Extant literature suggests that the influence of entrepreneurial capabilities and practices on business performance is inconclusive especially with the use of questionnaire surveys where the complexity of the contexts of study is overlooked. This study examines how Chinese SMEs’ entrepreneurial capabilities and practices are continuously developed in response to changing contextual circumstances in Malaysia. This study appraises the inextricable connection between the historical development of Malaysia and Chinese entrepreneurial capabilities and practices. In a case setting, this study further examines how a resilient Chinese SME overcomes various challenges and captures opportunities in the process of developing entrepreneurial capabilities and practices for more than four decades. Chinese SMEs are found to demonstrate a staunch desire for self-sufficiency and progress in the face of adversity. The case firm demonstrates constant upgrade in efficiency, effectiveness and contributions to the value chain, which reflects the very essence of entrepreneurship, i.e. from rags to riches. Results of this study serves as a guide for aspiring entrepreneurs. As for policy makers, this study sheds light on the importance of initiatives aimed at character-building to promote life-long learning among SMEs rather than financial assistance, which does little to encourage the quest for self-sufficiency.